2004
DOI: 10.1111/j.1751-3928.2004.tb00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Kanggur Gold Deposit in Eastern Tianshan Orogenic Belt, NW China: Fluid Inclusion and Oxygen and Hydrogen Isotope Constraints

Abstract: Primary fluid inclusions in quartz and carbonates from the Kanggur gold deposit are dominated by aqueous inclusions, with subsidiary CO 2 -H 2 O inclusions that have a constant range in CO 2 content (10~20 vol %). Microthermometric results indicate that total homogenization temperatures have a wide but similar range for both aqueous inclusions (120°to 310°C) and CO 2 -H 2 O inclusions (140°to 340°C). Estimates of fluid salinity for CO 2 -H 2 O inclusions are quite restricted (5.9~10.3 equiv. wt% NaCl), whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…Studies of orogenic gold deposits by, for example, Kerrich et al (2001) and Mao et al (2002b) in the past several years have shown that this type of gold deposit is characterized by the common presence of abundant carbonate veins or quartz–carbonate veins in the late stage, and it has been suggested by these authors that ore‐forming fluids contain high CO 2 concentrations which were, at least in part, derived from mantle fluids. Examples are the Kanggur gold deposit (Wang et al , 2004; Mao et al , 2005) and deposits in the Jiaodong gold province in China (Mao et al , . 2002b) and gold deposits in the Yilgarn Craton, Western Australia (Groves et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of orogenic gold deposits by, for example, Kerrich et al (2001) and Mao et al (2002b) in the past several years have shown that this type of gold deposit is characterized by the common presence of abundant carbonate veins or quartz–carbonate veins in the late stage, and it has been suggested by these authors that ore‐forming fluids contain high CO 2 concentrations which were, at least in part, derived from mantle fluids. Examples are the Kanggur gold deposit (Wang et al , 2004; Mao et al , 2005) and deposits in the Jiaodong gold province in China (Mao et al , . 2002b) and gold deposits in the Yilgarn Craton, Western Australia (Groves et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Microthermometric measurements and H and O isotopic compositions of fluid inclusions show that from the intrusion-related type through shear zone-hosted type to epithermal type, the temperature, depth, and salinity of gold deposits decrease, and that the ore-forming fluids change gradually from dominantly magmatic (and metamorphic) hydrothermal fluids to fluids with a significant meteoric water component (Ji et al, 1997;Mao et al 2002;Zhang et al 2003;Wang et al 2004). Sulfur isotope study shows that the sulfur in the gold metallogenic system was mainly derived from the mantle or the great depth of the Earth (Ji et al 1994;Zhang et al 2003).…”
Section: Discussionmentioning
confidence: 96%
“…The shear system controls the attitude, shape, size and distribution of the orebodies (Wang et al 2003). The isotopic compositions (Zhang et al 2003;Wang et al 2004) indicate that ore-forming fluids originated from the deep-seated source. In the light of development of the synkinematic granitoids in the Yamansu-Kushui fault belt, it appears that the magmatism is related to shear melting, which can also produce dynamometamorphic fluids.…”
Section: Nature Of Gold Mineralizationmentioning
confidence: 99%
“…The newly discovered Late Silurian granodiorite in the Tuwu–Yandong and Sanchakou deposit (Wang & Zhang, ; Xiao, Chen, Wang, & Yang, ) indicates that the Dananhu island arc and the Harlik island arc belong to the same island–arc system and were also created by a south‐dipping subduction of Kelameili oceanic plate (Deng, Wang, Pirajno, et al, ; Xiao et al, ). The Kanggur arc accretionary complex contains marine lavas and pyroclastic rocks that were thrust southward over the Yamansu arc (Xiao et al, ) and characterised by Carboniferous volcanic–sedimentary rocks and contains ductile shear zone‐hosted gold (Kanggur; Wang, Jiang, Wang, Mao, & Yang, ), Cu–Ni (Huangshan; Mao, Qin, & Barnes, ), and porphyry Mo (Baishan; Deng, Wang, Santosh, et al, ) deposits. The interpretation of the tectonic setting of the Kanggur arc is controversial, such as fore‐arc and inter‐arc basin origin (Ma et al, ; Xiao et al, ).…”
Section: Regional Geologymentioning
confidence: 99%